2000
DOI: 10.1046/j.1469-0691.2000.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of a resistant Pseudomonas aeruginosa strain after a cluster of infections in a hematology/oncology unit

Abstract: The potential for serious nosocomial infections with P. aeruginosa is well recognized. Eradication of the organism from the environment may require the co-ordinated efforts of clinicians, nurses, pharmacy and hospital engineers, working in collaboration with the hospital infection control team. To date, the same strains have not been isolated despite repeated surveillance over the past 18 months and therefore these measures have, in our opinion, successfully removed the potential for nosocomial infection with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…However the effect may be short term; one study showed that after 3-6 hours bacterial counts begin to rise again in many household sites, including in sink drain U-tubes [41]. Furthermore, eradication of epidemic strains of P. aeruginosa in hospital settings has in some cases only been achieved by complete replacement of sink drains [42,43], presumably due to higher resistance of P. aeruginosa in biofilms to disinfectants [44].…”
Section: Discussionmentioning
confidence: 99%
“…However the effect may be short term; one study showed that after 3-6 hours bacterial counts begin to rise again in many household sites, including in sink drain U-tubes [41]. Furthermore, eradication of epidemic strains of P. aeruginosa in hospital settings has in some cases only been achieved by complete replacement of sink drains [42,43], presumably due to higher resistance of P. aeruginosa in biofilms to disinfectants [44].…”
Section: Discussionmentioning
confidence: 99%
“…MRPA clones have been isolated in vectors such as bath toys [13] and plumbing circuits [14] in patients suffering from cancer. No vector was identified in our case; however, the epidemic was effectively eradicated once the control measures had been implemented.…”
Section: Discussionmentioning
confidence: 99%
“…The source of transmission was found to be drains that was detected by molecular profiling to be the only source to harbor KPC, persistently. Outbreak with P. aeruginosa , revealed that patients were not colonized on admittance, but acquired a multi-resistant P. aeruginosa during hospitalization [17]. By running antibiogram and molecular profiling, drains were found to be the only source.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Pseudomonas aeruginosa Sink drainsHematology unit, Lund, SwedenDagens Nyheter [15]ESBL Klebsiella pneumoniae Sink drainsNeurosurgical ICU, Uppsala, SwedenStarlander et al . [5] Klebsiella pneumonia Carbapenem resistantSink drainsICU, Sørlandet, NorwayTofteland et al [16] Pseudomonas aeruginosa DrainsICU, Edinburgh, UKGillespie et al [17]ESBL EnterobacteriaceaeSink drainsICU, Tours, FranceRoux et al [18]Carbapenem-resistant P. aeruginosa Unsealed drainUrology ward, Barcelona, SpainPeña et al [19] P. aeruginosa with unusual antibiogramDrainsNeurosurgery ICU, Clichy, FranceBert et al [20]ESBL Klebsiella oxytoca Sink drainsHospital, Toronto, CanadaLowe et al [21]Foot Mouth Disease virusLeaking drainsCommunity, Pirbright, UKHSE [22] P. aeruginosa Grooved drainage designHaemotology, SingaporeLing and How [23]Carbapenem resistant Klebsiella oxytoca Drainpipes, trapsICU, SpainVergeres -Lopez et al [24]…”
Section: Introductionmentioning
confidence: 99%